Measurements and Analysis of Sound Reflections from Selected Building Façades - Adam Zagubień; Katarzyna Wolniewicz (Applied Sciences)
This paper presents a study of the effect of the type of exterior cladding material of a building façade on the amount of sound reflection. It was verified whether there is a sound field undisturbed by reflections, similar to the free field, at a distance of 3 m from the building façade. Sound reflections from three building façade structures were tested: clinker brick, mineral plaster, and hard HPL. An equal geometry of the measuring field at selected real objects was used. It was determined that the differences in sound level results measured at distances up to 2 m and more than 2 m from the building façade are lower than the −3 dB correction specified in ISO 1996-2. Significant differences were observed comparing the measured sound level values in the undisturbed sound field with the levels recorded at a distance of 3 m from the building façade. It was proposed that the results of measurements made to control the levels of permissible noise in the environment should not be subject to the −3 dB correction.